Higher cerebrospinal fluid (CSF) opening pressure in patients with idiopatic intracranial hypertension (IIH) with permanent visual impairment - Domingues, Renan; Senne, Carlos; Lacerda, Cassio Batista (Headache Medicine, 2022)
Objective The aim of this study was to identify potential visual prognostic markers in patients with idiopathic intracranial hypertension (IIH). Methods Patients with IIH of an outpatient headache clinic in São Paulo, Brazil, were retrospectively evaluated and divided in two groups with and without the presence of permanent visual deficit attributed to IIH. Body mass index (BMI), opening CSF pressure, and the frequency of IIH related MRI abnormalities were compared between these two groups. Results Twenty-nine patients, with 35,39±9,93 years, being twenty-eight female (96.55%) were included in the study. Reduced visual acuity attributed to IIH was registered in 16 (55.17%). According to BMI 17.4% had overweight and 82.6% were obese. Brain MRI was normal in 6 (20.69%). BMI, obesity, and the presence of MRI abnormalities were not associated with visual impairment. Initial CSF opening pressure was significantly higher in the group of patients with reduced visual acuity (40.4±13.14 x 30.5±3.41, P=0,015). Conclusion Higher CSF opening pressure at onset was significantly associated with a higher percentage of visual impairment in patients with IIH suggesting this measure as a potential prognostic marker for patients with IIH.